2017
DOI: 10.1016/j.ebiom.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Global Proteome and Phospho-proteome Analysis of Merlin-deficient Meningioma and Schwannoma Identifies PDLIM2 as a Novel Therapeutic Target

Abstract: Loss or mutation of the tumour suppressor Merlin predisposes individuals to develop multiple nervous system tumours, including schwannomas and meningiomas, sporadically or as part of the autosomal dominant inherited condition Neurofibromatosis 2 (NF2). These tumours display largely low grade features but their presence can lead to significant morbidity. Surgery and radiotherapy remain the only treatment options despite years of research, therefore an effective therapeutic is required.Unbiased omics studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 80 publications
1
31
0
Order By: Relevance
“…Future work is required to elucidate the role of M2 macrophages in meningiomas, and to uncover the mechanisms in which tumour cells harbouring a mutation such as AKT1 E17K can directly affect the tumour microenvironment. From proteomics studies [36,37] published by our group and others, it is clear that the tumour microenvironment of meningiomas is highly heterogeneous, and that linking cell population, gene expression and/or signalling pathway activation data to genetically defined non-NF2 and NF2 groups would be very beneficial. The simple, cost-effective endpoint genotyping technique used here could aid such stratification in any research or clinical laboratory with a real-time PCR instrument.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work is required to elucidate the role of M2 macrophages in meningiomas, and to uncover the mechanisms in which tumour cells harbouring a mutation such as AKT1 E17K can directly affect the tumour microenvironment. From proteomics studies [36,37] published by our group and others, it is clear that the tumour microenvironment of meningiomas is highly heterogeneous, and that linking cell population, gene expression and/or signalling pathway activation data to genetically defined non-NF2 and NF2 groups would be very beneficial. The simple, cost-effective endpoint genotyping technique used here could aid such stratification in any research or clinical laboratory with a real-time PCR instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Domingues et al [26] clearly demonstrated that it is possible to detect tumour-associated macrophages in single-cell suspensions using mechanical disaggregation by multicolour flow cytometric immunophenotyping, and we therefore decided to use this technique to quantify the immune infiltrates in our well established primary cell culture model [37] and to correlate these results to mutational hotspots.…”
Section: Detection Of M2 Macrophages By Four-colour Flow Cytometrymentioning
confidence: 99%
“…Proteins were separated on a Laemmli SDS-PAGE, and transferred to a polyvinylidene di uoride membrane (Immun-Blot® PVDF Membrane, Bio-Rad). Membrane blocking, antibody incubation, and washes were performed as previously described (21). (sc-59286, RRID:AB_784278) and anti-Calnexin (sc-46669, RRID:AB_626784) were purchased from Santa Cruz Biotechnology (USA), while anti-GM130 (clone 35, RRID:AB_398142) and GAPDH (#MAB374, RRID:AB_2107445) were from BD Biosciences (UK) and Millipore (USA), respectively.…”
Section: Western Blottingmentioning
confidence: 99%
“…The malignant meningioma cell line KT21-MG1 (RRID:CVCL_M429) was cultured as previously reported (20). The benign meningioma cell line Ben Men-1 (RRID:CVCL_1959), and the malignant meningioma cell line IOMM-Lee (RRID:CVCL_5779) were both maintained as in (21). WHO I primary meningioma cells were obtained as reported in (22) Gene expression levels were computed using the quantitative 2 -(ΔΔCt) method, employing the HMC as calibrator, in triplicate (24).…”
Section: Introductionmentioning
confidence: 99%
“…Bassiri et al . aimed at identification of novel drug targets for Merlin‐deficient meningioma and schwannoma through parallel analysis of proteome and phosphoproteome in schwannoma/schwann cells and meningioma/meningeal cells.…”
Section: Discovery Of Potential Drug Targetsmentioning
confidence: 99%